Frontotemporal Dimentia (FTD), Late Onset Secondary to Total Abdominal Hysterectomy-Bilateral Salpingo-Oophorectomy: A Case Report in Malaysia - Rosliza, Yahaya; Ahmad Zubaidi, A.latif; Nordin, Simbak; Atif Amin, Baig (2018)
The relationship between cognitive impairment and depression were established. However, the exact mechanism is virtually unknown. Frontotemporal dementia (FTD) is second most common type of dementia after Alzheimer’s disease. To date, there is no proposed specific treatment for FTD, the mainstay of treatment is a combination of symptomatic pharmacological and psychosocial or behavioural intervention. The connection between FTD and level of estrogen was poorly understood. Interestingly recent findings reflect that there is association between estrogen use and development of FTD. Primary function of estrogen is in the development of sexual characteristics. Apart from that, it plays a vital role in the metabolism and mental health. Abrupt reduction of estrogen level in the blood and internal sustained low level of estrogen correlate with significant mood and cognitive changes. Estrogen replacement therapy (ERT) introduced to as a treatment for menopause, but it has linked with increased risk for breast cancer and thromboembolism phenomenon. We describe the case of post-menopausal women secondary to TAHBSO with underlying treatment-resistant major depressive disorder presented with cognitive disturbance. This case illustrates a challenge in the determination of correct diagnosis and decision of appropriate management that subsequently can affect the prognosis.